Multi-scalar response of an experimental fixed-wall meandering channel to a sediment supply increase - Cortese, David, author; Nelson, Peter, advisor; Morrison, Ryan, committee member; Wohl, Ellen, committee member (Colorado State University. Libraries, 2020)
Meandering river planforms are prevalent and well-studied features in the natural landscape. These rivers commonly exhibit a characteristic morphology of fine-grained point bars along the inner banks of meander bends with coarser pools along the outer banks. If subjected to a change in sediment supply, these rivers are likely to respond at various spatial and temporal scales through adjustments to sorting patterns, cross-sectional shape, and reach-scale morphology. In this study, a flume experiment was conducted to document the temporal progression of responses across scales of a fixed-wall meandering channel to a sediment supply increase. The 0.344 m wide experimental channel consisted of four meander bends following a sine-generated trace with a 20-degree crossing angle, meander wavelength of 2.75 m, and a unimodal sediment mixture with median grain size of 0.62 mm. The channel was provided constant flow and sediment supply until an initial equilibrium was established, after which the sediment supply was doubled until a new equilibrium state was reached. The experimental channel developed characteristic bar-pool morphologies and sorting patterns with superimposed, mobile, scaled gravel-dune bed forms during both phases of the experiment. After the sediment supply increase, dynamic adjustments occurring from smaller to larger scales took place. Initially, the dunes essentially disappeared, after which the relief of the bars decreased. Both of these sub-reach-scale responses were temporary, however, and ultimately the dunes and bar-pool morphology returned to their conditions at the beginning of the sediment supply increase. The long-term and largest-scale response to the supply increase was a 44% increase in bed slope. To explain these observations, we propose a conceptual model wherein the channel undergoes a temporal progression of responses from smaller to larger spatial scales, with the total response potential at each scale related to the conditions and constraints at that scale. This conceptual understanding allows us to reconcile seemingly divergent outcomes from previous research on how meandering rivers adjust to sediment supply changes.
Keywords: flume experiment; gravel-bed river; sediment supply; geomorphology; channel response; meandering river